Electrophoretic deposition of carbon nanotubes on heat spreader for fabrication of thermal interface materials (TIM) - Raihana Bahru,; Abdul Rahman Mohamed,; Yeoh, Wei-Ming; Khatijah Aisha Yaacob, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Thermal interface materials (TIMs) are applied in packaging of electronic devices for heat dissipation purposes. Carbon nanotubes (CNTs) are promising material due to their high thermal conductivity properties which will give optimum performance as TIMs. In this research study, electrophoretic deposition (EPD) is used which enables the deposition process conduct at room temperature with simple equipment setup which beneficial for CNTs deposition. As-produced CNTs was purified and directly deposited on heat spreader using direct current (DC) electricity. Dimethylformamide (DMF) was used as suspension medium for CNTs and the effect of suspension concentration was studied. From the screening of suspension concentration, 0.50 mg/mL yielded good deposition with thickness of 4.78 μm of CNTs deposited on heat spreader at applied voltage of 150V and 10 min deposition time. Further studied in different applied voltage and voltage of 250 V shows the maximum thickness of 15.01 μm with 2.0 mg weight of deposited CNTs which is suitable for fabrication of TIM.